Motivasi Terselubung Gerakan Politik dan Fundamentalis terhadap Muslim - Indra Harahap; Rhabliani Matondang (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2023)
This study analyzes the roots of fundamentalist Islamic political movements in the modern era by specifically exploring the logic in Islamic theology that is specific to Islamic fundamentalists. On that basis, this research attempts to critically dissect how Armstrong perceives Islamic fundamentalist political ideology. The Islamic fundamentalist movement, in particular, must be understood as a political movement. With this assumption, the position of the fundamentalists and the way they struggle and the ideological basis can be seen clearly. Based on the above themes, this study concludes two important findings: first, many forms of what is called